2020
DOI: 10.1128/msphere.00670-20
|View full text |Cite
|
Sign up to set email alerts
|

Natural Infection with Giardia Is Associated with Altered Community Structure of the Human and Canine Gut Microbiome

Abstract: Enteric parasitic infections are among the most prevalent infections in lower- and middle-income countries (LMICs) and have a profound impact on global public health. While the microbiome is increasingly recognized as a key determinant of gut health and human development, the impact of naturally acquired parasite infections on microbial community structure in the gut, and the extent to which parasite-induced changes in the microbiome may contribute to gastrointestinal symptoms, is poorly understood. Enteric pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 100 publications
5
49
4
Order By: Relevance
“…Conversely, Giardia infection was correlated with a decrease of Natronobacillus , Lactobacillus , and Leuconostoc . Similar results were observed in MAL-ED participants (Peru), where Giardia Infection was associated with an enrichment of Prevotella and a reduction in Escherichia (Gammaproteobacteria; Berry et al, 2020 ). LEfSe also revealed an association between Giardia infection and an increase of Faecalibacterium , Blautia , Roseburia , Ruminococcus , and Ruminoccaceae , and an increase of Lachnospiraceae and Lactobacillus contrary to the GEMS study.…”
Section: Alterations To the Microbiota During Giardia supporting
confidence: 79%
See 3 more Smart Citations
“…Conversely, Giardia infection was correlated with a decrease of Natronobacillus , Lactobacillus , and Leuconostoc . Similar results were observed in MAL-ED participants (Peru), where Giardia Infection was associated with an enrichment of Prevotella and a reduction in Escherichia (Gammaproteobacteria; Berry et al, 2020 ). LEfSe also revealed an association between Giardia infection and an increase of Faecalibacterium , Blautia , Roseburia , Ruminococcus , and Ruminoccaceae , and an increase of Lachnospiraceae and Lactobacillus contrary to the GEMS study.…”
Section: Alterations To the Microbiota During Giardia supporting
confidence: 79%
“…Among the GEMS participants, 215 individuals tested positive for Giardia and were subclassified as having either moderate to severe diarrhea (MSD) or no MSD. Metagenomic biomarker discovery analysis (LEfSe score) revealed that Giardia infection was associated with an enrichment of Prevotella and a reduction in Gammaproteobacteria, regardless of the presence of mild to severe diarrhea ( Berry et al, 2020 ). To a lesser extent, Giardia infection was also associated with an increase of Lachnospiraceae , Ruminococcus , and Clostridiales .…”
Section: Alterations To the Microbiota During Giardia mentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, Saccharomyces boulardii showed a potential benefit for the treatment of acute gastroenteritis in paediatric patients [29]. More interestingly, Blastocystis is usually associated with a "healthy" gut microbiota whereas Giardia is usually associated with gut dysbiosis [29,30]. Thus, whether the wood decaying Coriticiaceae Stereum hirsutum, or the common human opportunistic pathogenic yeast Candida tropicalis are associated with a dysbiotic or a healthy gut microbiota warrant further studies.…”
Section: Discussionmentioning
confidence: 99%